Keeping the competition close: The impact of competitor distance in the lodging industry. (19th January 2022) - Park, Chansoo; Kim, Young‐Rae; Frye, William D.
Abstract: This study applies a distance‐based measurement outlining market boundaries for competition in the lodging industry and investigates the effects of competition across a range of distances. Predetermined administrative boundaries have been the conventional metric used when estimating competition effects in a given geographical area in the lodging industry. For this study, distances are calculated using the location information of 45, 623 hotels in the United States extracted from the Smith Travel Research Hotel Census. Our findings suggest a U‐shaped relationship: hotel room prices fall as relative distance increases, due to increasing negative price pressure, until a threshold distance is reached (a radius of 20 km), after which price pressure falls and prices begin to increase. These research findings have implications for hotel managers with respect to competitor management and for hotel investors interested in locating and developing future accommodation establishments.